Turning the ′Tides on Neuropsychiatric Diseases: The Role of Peptides in the Prefrontal Cortex - Brockway, Dakota F.; Crowley, Nicole A. (Frontiers in Behavioral Neuroscience, 2020)
Recent advancements in technology have enabled researchers to probe the brain with greater region, cell, and receptor specificity. These developments have allowed for a more thorough understanding of how regulation of the neurophysiology within a region is essential for maintaining healthy brain function. Stress has been shown to alter prefrontal cortex (PFC) functioning, and evidence links functional impairments in PFC brain activity with neuropsychiatric disorders. Moreover, a growing body of literature highlights the importance of neuropeptides in the PFC to modulate neural signaling and to influence behavior. The converging evidence outlined in this review indicates that neuropeptides in the prefrontal cortex are specifically impacted by stress, and are found to be dysregulated in numerous stress related neuropsychiatric disorders including substance use disorder, major depressive disorder, posttraumatic stress disorder, and schizophrenia. This review explores how neuropeptides in the PFC function to regulate neural activity, and how genetic and environmental factors, such as stress, lead to dysregulation in neuropeptide systems, which may ultimately contribute to the pathology of neuropsychiatric diseases.